2021
DOI: 10.1007/s40268-021-00372-1
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 in the Treatment of Heart Failure with Preserved Ejection Fraction: A Prospective, Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Background Heart failure with preserved ejection fraction (HFpEF) is common in elderly people and is increasing in prevalence. No specific treatment for this condition exists. Coenzyme Q10 (CoQ10) is an essential cofactor for energy production, with reduced levels being noted in HF. Previous studies have suggested a possible role for CoQ10 in the treatment of HF. This study examined the effect of CoQ10 supplementation on diastolic function in HFpEF patients. Methods We conducted a prospective, randomized, doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…In contrast to that, CoQH2 studies included test concentrations between 300 and 600 mg/day. The only CoQH2 study using 300 mg/ day test concentration included only 39 patients, and no beneficial cardiovascular effects could be observed [42].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to that, CoQH2 studies included test concentrations between 300 and 600 mg/day. The only CoQH2 study using 300 mg/ day test concentration included only 39 patients, and no beneficial cardiovascular effects could be observed [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, current studies on CoQ10 improving myocardial diastolic function have shown conflicting results. Adarsh et al [ 81 ] showed that CoQ10 significantly improved exercise tolerance and diastolic dysfunction in patients with hypertrophic cardiomyopathy, but no positive results were shown in two other studies [ 82 , 83 ]. This may be due to differences in the diastolic function assessment criteria and biologic agents (ubiquinone and ubiquinone alcohol) that led to changes in bioavailability [ 84 ]; thus, the effectiveness of CoQ10 needs further confirmation.…”
Section: Research Progress Of Anti-ferroptosis In Hfpefmentioning
confidence: 99%
“…Примечание ремоделирование и функциональное состояние ЛЖ, а также снижение риска смерти и повторных госпитализаций [1,12,131,132]. Продолжается разработка и клиническое тестирование потенциально эффективных при ХСН миокардиальных цитопротекторов, направленных на торможение окисления жирных кислот, стимуляцию окисления глюкозы, активцию цитохромной цепи, оптимизацию транспорта энергетического субстрата в митохондрии, а также повышение антиоксидантного потенциала кардиомиоцита [4,[133][134][135][136][137][138][139][140][141][142][143] Коррекция гиперкалиемии, которая классифицируется как легкая (5,0-5,4 ммоль/л), умеренная (5,5-6,0 ммоль/л) и тяжелая (>6,0 ммоль/л).…”
Section: лечебные подходыunclassified